Diversity in intermediate care - Martin, Graham P.; Peet, Susan; Hewitt, Graham; Parker, Hilda (2004)
This paper discusses the evolution of intermediate care and presents some interim observations from a survey of providers in England being conducted as part of a national evaluation of intermediate care. Telephone interviews covering various issues concerning the level of provision and style of delivery of intermediate care have been conducted with 70 services to date. Data from these are used to discuss the progress, range and nature of intermediate care in relation to clinician viewpoints and academic and official literature on the subject. Intermediate care ‘on the ground’ is a multiplicitous entity, with provision apparently evolving in accordance with the particularities of local need. Whilst protocols for medical involvement in intermediate care generally appear to be well established, there are some tensions concerning integration of services in a locality, care management processes and questions of flexibility and inclusiveness in relation to eligibility criteria. The definitive version is available at www.blackwell-synergy.com